Offline solutions for agricultural extension: Integrating digital libraries into train-the-trainer programs - Laura Hosman; Rachel Nova (Advancements in Agricultural Development)
Training agricultural extension workers to educate rural farmers on conservation agriculture (CA) techniques is a significant challenge, especially in areas with limited access to the internet. This article evaluates the effectiveness of a train-the-trainer (TTT) approach that integrates an offline digital library and competency-based training to address both the information and skills needs of extension agents in Rwanda. Using Harper et al.'s (2024) TTT framework, the study assesses a TTT workshop conducted with agriculture extension interns, focusing on their ability to train farmers in CA practices. The training combined access to SolarSPELL, a portable offline library, with interactive learning experiences to enhance both technical and interpersonal skills. Post-training survey results indicate that participants found the digital library highly beneficial in overcoming information access challenges, while the competency training equipped them with essential skills for their roles. The findings suggest that integrating digital tools into TTT programs, particularly in rural offline settings, can enhance knowledge dissemination and improve the efficacy of agriculture training programs. The article explores the implications for broader adoption of this approach in other regions and agricultural sectors.